The pharmacokinetic and pharmacodynamic interaction of clopidogrel and cilostazol in relation to CYP2C19 and CYP3A5 genotypes - Kim, Ho‐Sook (Br J Clin Pharmacol, 2015)
AIM: The primary objective of the present study was to evaluate the pharmacokinetic and pharmacodynamic interactions between clopidogrel and cilostazol in relation to the CYP2C19 and CYP3A5 genotypes. METHODS: In a randomized, three‐way crossover study, 27 healthy subjects were administered clopidogrel (300 mg), cilostazol (100 mg) or clopidogrel + cilostazol orally. Plasma concentrations of clopidogrel, cilostazol and their active metabolites (clopidogrel thiol metabolite, 3,4‐dehydrocilostazol and 4″‐trans‐hydroxycilostazol), and adenosine diphosphate‐induced platelet aggregation were measured for pharmacokinetic and pharmacodynamic assessment. RESULTS: The area under the plasma concentration–time curve (AUC) of the active thiol metabolite of clopidogrel was highest in the CYP2C19 extensive metabolizers (EM) and lowest in the poor metabolizers (PM). Cilostazol decreased the thiol metabolite AUC by 29% in the CYP3A5*1/*3 genotype [geometric mean ratio (GMR) 0.71; 90% confidence interval (CI) 0.58, 0.86; P = 0.020] but not in the CYP3A5*3/*3 genotype (GMR 0.93; 90% CI 0.80, 1.10; P = 0.446). Known effects of the CYP2C19 and CYP3A5 genotypes on the exposure of cilostazol and its metabolites were observed but there was no significant difference in the AUC of cilostazol and 3,4‐dehydrocilostazol between cilostazol and clopidogrel + cilostazol. The inhibition of platelet aggregation from 4 h to 24 h (IPA(4–24)) following the administration of clopidogrel alone was highest in the CYP2C19 EM genotype and lowest in the CYP2C19 PM genotype (59.05 ± 18.95 vs. 36.74 ± 13.26, P = 0.023). However, the IPA of the CYP2C19 PM following co‐administration of clopidogrel and cilostazol was comparable with that of the CYP2C19 EM and intermediate metabolizers (IM) only in CYP3A5*3/*3 subjects. CONCLUSIONS: The additive antiplatelet effect of cilostazol plus clopidogrel is maximized in subjects with both the CYP2C19 PM and CYP3A5*3/*3 genotypes because of a lack of change of clopidogrel thiol metabolite exposure in CYP3A5*3/*3 as well as the highest cilostazol IPA in CYP2C19 PM and CYP3A5*3/*3 subjects.